2012
DOI: 10.1155/2012/753949
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Electron Transport at the Onset of Reperfusion Decreases Cardiac Injury in Aged Hearts by Protecting the Inner Mitochondrial Membrane

Abstract: Myocardial injury is increased in the aged heart following ischemia-reperfusion (ISC-REP) compared to adult hearts. Intervention at REP with ischemic postconditioning decreases injury in the adult heart by attenuating mitochondrial driven cell injury. Unfortunately, postconditioning is ineffective in aged hearts. Blockade of electron transport at the onset of REP with the reversible inhibitor amobarbital (AMO) decreases injury in adult hearts. We tested if AMO treatment at REP protects the aged heart via prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…The brief, transient blockade of electron transport by amobarbital at the onset of reperfusion decreases myocardial injury in adult rat heart 15; 57 and rabbit heart. 57; 58 Initial results in the aged heart 59 suggest that the modulation of electron transport for a brief period at the onset of reperfusion reduces injury consistent with the important principal advanced in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…The brief, transient blockade of electron transport by amobarbital at the onset of reperfusion decreases myocardial injury in adult rat heart 15; 57 and rabbit heart. 57; 58 Initial results in the aged heart 59 suggest that the modulation of electron transport for a brief period at the onset of reperfusion reduces injury consistent with the important principal advanced in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with these findings, reversible pharmacological blockade of electron transport at the onset of reperfusion was recently reported to decrease cardiac injury in aged hearts by improving the inner mitochondrial membrane potential. 32 …”
Section: Discussionmentioning
confidence: 99%
“…These authors suggest that during early minutes of reperfusion, postconditioning reduces oxidative stress and inhibits mPTP opening independent of alteration in oxidative phosphorylation and mitochondrial membrane potential (94). Fischer 344 rat hearts undergoing 25 min of global ischemia and 30 min of reperfusion when treated with amobarbital for 3 min at the onset of reperfusion display decreased cardiac injury as well as improved IMM potential in both subpopulations, indicating preserved IMM integrity (15). Using a Langendorff perfused rat heart model of 25 min of global ischemia followed by 30 min of reperfusion, Chen et al (14) reported improved Ca 2ϩ tolerance and IMM potential in the SSM subpopulation.…”
Section: Pathological Influencementioning
confidence: 98%
“…Inherently, aging has been shown to decrease IFM oxidative metabolism; however, Lesnefsky et al (73) observed restoration of ETC complexes III and IV activities and oxidative phosphorylation in the IFM following 25 min of ischemia and 30 min of reperfusion in the aged rat heart pretreated with acetylcarnitine. Using a similar I/R protocol, Chen et al (15) observed preservation of IMM potential and integrity in both SSM and IFM when amobarbital treatment was presented at reperfusion. Taken together, these studies indicate that pharmacological modulation of electron transport may present an avenue for decreasing mitochondrial injury brought about by I/R in the aged heart.…”
Section: Pathological Influencementioning
confidence: 99%